Evaluation of the bonded ratio of TC4 diffusion bonded joints based on ultrasonic C-scan. (November 2019) - Xiong, J.T.; Sun, J.R.; Wang, J.C.; Zhang, H.; Shi, J.M.; Li, J.L.
Abstract: The immersion ultrasonic C-scan ((IUCT) test was conducted for evaluating the bonded ratio of the TC4 diffusion bonded joints. The signal characteristics reflected by the typical bonding states of the joint, gap, kissing bond, microvoids and sound bond were investigated in the time and frequency domain. Moreover, as for the bonding state of microvoids, its local bonded ratio exhibited a linear relationship with the relative amplitude of its echo signal in the time domain. Based on the echo signal characteristics and the linear relationship about microvoids, a MATLAB algorithm program was developed to calculate the global bonded ratio of bonding interface directly from echo signal of IUCT. The results demonstrated that joint bonded ratio and mechanical properties, especially the tensile strength, could be quantitively evaluated by the combination of IUCT test and the developed MATLAB program.